Cone Beam Computed Tomography Assessment of the Volume of Dental Tissue Removed During Endodontic Access - Chaves, Gustavo Silva; Estrela, Carlos; Silva, Fernanda Paula Yamamoto; Silva, Julio Almeida; Alencar, Ana Helena GonÃ§alves; Decurcio, Daniel de Almeida (Iranian Endodontic Journal, 2021)
Introduction: The purpose of this study was to determine the volume of dental tissue removed during endodontic access preparation with cone-beam computed tomography (CBCT) comparing two different software. Methods and Materials: CBCT images of 20 teeth were obtained before and after endodontic access performed with spherical and conical diamond burs. The images were taken with i-CAT Precise system with 0.25 mm voxel size. Digital Imaging and Communications in Medicine (DICOM) images were loaded on two different software programs (Materialise® and InVersalius®), and a 3D reconstruction of the CBCT images was performed on both programs. The baseline volume (BV), and the final volume (FV) were obtained, and the lost tissue volume (LV) was calculated using the formula: LV=BV-FV. The t-test was used to compare initial and final volumes and also to compare the two programs, using a significance level of 5%. Results: The volumetric data calculated for the MaterialiseÒ and the InVesaliusÒ programs were, respectively: BV-mean of 441.79±85.08 mm3 and 442.01±84.83 mm3; FV-mean of 426.75±83.88 mm3 and 426.94±83.75 mm3; LV-mean of 15.04±4.32 mm3 and 15.07±4.16 mm3. No statistically significant difference was found in the volumes calculated by either program for initial, final, or removed tissue (P>0.05). However, there was a significant difference between the BV and LV calculated on the same program (P<0.05). Conclusion: Our in vitro study showed that CBCT was able to determine the volume of dental tissue removed in the endodontic access preparation of extracted human teeth, regardless of the software program used.